1993
DOI: 10.1088/0031-9155/38/11/011
|View full text |Cite
|
Sign up to set email alerts
|

Effect of blood perfusion on the ablation of liver parenchyma with high-intensity focused ultrasound

Abstract: This paper discusses the effect of blood perfusion on the ablation of rat liver tissue with high-intensity focused ultrasound (HIFU). For this study a practical method has been developed, in which the liver blood flow can be reduced by ligation of the hepatic artery and portal vein. During the treatment the rat liver was mobilized out of the abdomen and the blood flow was measured using both the radioactive microsphere method and a laser Doppler blood-flow monitor. The results show that the hepatic blood flow … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
63
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(70 citation statements)
references
References 11 publications
7
63
0
Order By: Relevance
“…For example for 6 W and 60 s duration the in vitro experiments the depth of lesion is approximately 15 mm. Using the same exposure in vivo, the depth of lesion is 12 mm which is attributed to the perfusion effect [58].…”
Section: Discussionmentioning
confidence: 97%
“…For example for 6 W and 60 s duration the in vitro experiments the depth of lesion is approximately 15 mm. Using the same exposure in vivo, the depth of lesion is 12 mm which is attributed to the perfusion effect [58].…”
Section: Discussionmentioning
confidence: 97%
“…We observed that complete electrical PV isolation was significantly more common when no blood flow leaks were identified between PV tissue and balloon catheter ablation, which determines the importance of catheter-balloon tissue contact also with laser energy. Good contact between the balloon and the PV orifice is necessary to obtain a circumferential lesion [14][15][16][17] . These requirements are probably related to photothermal and photomechanical interactions between laser energy on the tissue and heat transfer, which can be influenced by blood stream and tissue characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…Increments were -27. 27-16.67%, 2.38-37.50% and 20.45-45.00% at 3, 6 and 12 s-insonation (106-266 W/cm 2 at 1.7 MHz), respectively (Chen et al, 1991). This technique, therefore, has a poor clinical relevancy.…”
Section: Preclinical Findingsmentioning
confidence: 99%